A review on the treatment of septage and faecal sludge management: A special emphasis on constructed wetlands. (1st August 2022) - Jain, Mahak; Upadhyay, Maharishi; Gupta, Ashok Kumar; Ghosal, Partha Sarathi
Abstract: The global concern of the pollution of freshwater resources is associated with faecal sludge (FS) disposal, which is an inevitable component of onsite wastewater management mostly in developing countries. The difficulties with its treatment facilities lies in its higher organic content and low dewaterability of various available treatment systems. Moreover, the higher variability in characteristics and quantity of FS generated at different locations creates hindrances in designing the treatment system. Among the several treatment options, the constructed wetlands (CW) are an organic/green approach towards sanitation of FS with low cost and higher efficiency. The present study is an in-depth literature review on the quality and quantity of FS and septage (stabilized FS) in different regions attributed to the wide variability of its characteristics. This paper highlights the treatment of FS in different systems with a special emphasis on CW systems. Different mechanisms and factors affecting the FS treatment efficacy in CW, such as DO/aeration, macrophytes, substrate, CW configuration, and other environmental parameters, have been studied meticulously. The cost analysis revealed CW to be an economic system, and it can enable hybridization with other technologies to develop a complete treatment system with pronounced efficiencies. Several process modifications, such as augmentation with aeration, recirculation, micro-organisms, and earthworms, can enhance the treatment efficacies of CWs. The present review exhibited that the widely used plant species is Phragmites, and the optimum solid loading rate (SLR) range is 50–250 kg TS/m 2 /yr. The various factors to construct an optimized CW system for FS treatment were attempted, which may bolster the necessary guidelines for field-scale applications. Graphical abstract: Image 1 Highlights: FS and septage comprise of highly variable range of contaminants. Quantification reveals disparity in FS volume generated at various locations. Major factors affecting efficacy of CW were plants, DO, and substrate. Most used species was Phragmites sp. and SLR range was 50–250 Kg TS/m 2 /yr. High free board, DO, recirculation, and bio-augmentation boost sustainability of CW.